(3GdLGeY GdUMjMs - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s
(3ChdgG (B:s
(3cJGH GdML HGH hLhH GdML haVdg hbQd Gddg JYGdi (B: (3hddg Ydi GdfGS ML GdHjJ ef GSJWGY Edjg SHjdG s
(3BNQgG (B:s
(3HHGH EKe GdZGOQ ddeHQ hGdaGLQ ef cJGH aVd GdLgGO hGdSjQ , abGd GdYHGS jG QShd Gddg s
(3HChd GdfSNI bQGAI SfI (B493 (3dCHi YeQGf ehSi Hf SYGOI hYQaJ GdfSNI HfSNI GHf SYGOI hJYQa CjVkG HGdTjNI hddeZGQHI Ydi gPg GdfSNI cdGe cKjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs